An Investigation on the Perceptions of Practicing Interdisciplinary Health Professionals on Rapid Cycle Deliberate Practice Simulation. Issue 1 (February 2022) - Roszczynialski, Kelly N.; Register, Shilpa J.; Bergman, Lisa; White, Marjorie Lee
Abstract : Introduction: Rapid cycle deliberate practice (RCDP) is a relatively new method for delivering simulation for a structured algorithm-based clinical content. We sought to understand how a group of practicing emergency medicine healthcare professionals would perceive RCDP as a learning method. Methods: This was a qualitative study of participants' reactions to RCDP simulation during an orientation process to a new freestanding emergency department using grounded theory. Focus groups were held after simulation sessions to investigate the participants reactions to RCDP as well as the experience of multiple professions participating. Two investigators independently coded the focus group transcripts to detect themes and developed a list of codes, which were then confirmed by consensus. Data were organized into themes with contributing codes. Results: Thirty-one individuals participated in the focus groups including physicians, nurse practitioners, nurses, respiratory therapists, and patient care technicians. Four themes were detected: the procedural components of RCDP, the behavioral response to RCDP, learning through RCDP, and RCDP as interprofessional experience. The participants view of emotions and interruptions and pauses had discrepant interpretation. Conclusions: Participants received RCDP simulation positively. Initial negative reactions to the interruptions and pauses of RCDP dissipated as the simulation progressed. Ultimately, learners agreed that RCDP was extremely effective as compared with traditional simulation for medical resuscitation training because of the authenticity of the multidisciplinary aspect. This suggests that RCDP may be an effective tool for continuing education of practicing healthcare professionals. Abstract : Supplemental digital content is available in the text.